Unique Uses of SPY: High-risk Facelift - Kislevitz, Mikaela L. (Plast Reconstr Surg Glob Open, 2019)
Skin flap necrosis occurs in 1–3% of facelift procedures. The SPY Elite Fluorescence Imaging System has been widely used in evaluating mastectomy skin flaps for breast reconstruction but has not been described in assessing skin flaps during facelifts. This case report describes the intraoperative use of SPY to assess flap perfusion during a high-risk facelift and static sling for the correction of facial paralysis. The use of intraoperative SPY during this high-risk facelift allowed for the timely assessment of perfusion, successful intervention of nitroglycerin paste to improve blood flow, and prevention of any additional surgical interventions. SPY may have a more widespread role in facelift patients with a higher risk of skin flap necrosis.